Assessing potential conflicts between offshore wind farms and migration patterns of a threatened shorebird species - Schwemmer, P.; Pederson, R.; Haecker, K.; Bocher, P.; Fort, J.; Mercker, M.; Jiguet, F.; Elts, J.; Marja, R.; Piha, M.; Rousseau, P.; Garthe, S.
2022